'Making it work: widening participation in higher education for adults in employment'. (25th April 2015) - Merrill-Glover, Kirsten; Edwards, Kelly
Recent decades have seen an increasing acknowledgement of the positive contributions to be made by higher education interventions targeting adults in the workplace. In addition to the economic benefits associated with workforce development, it has been widely asserted that accredited work-based learning (WBL) activities present opportunities for engagement in higher education for employed individuals who might not otherwise consider a more traditional university programme (Helyer, 2008; Lester and Costley, 2010; Edwards, 2013). This paper exemplifies the models of delivery developed within the Faculty of Business & Society at the University of South Wales (USW). Through a consideration of the curriculum offer, teaching, learning, and assessment strategies, the paper contextualises models of delivery within broader debates around work-based learning, widening participation and personal and professional development. With an increasing emphasis being placed on vocational higher education, attention is drawn to contemporary debates around what constitutes knowledge and the perceived power differentials between academic subject areas, pedagogy and assessment strategies.